1997
DOI: 10.1182/blood.v90.1.21.21_21_27
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stroma-Derived Prolactin Is Involved in Basal and Platelet-Activating Factor–Stimulated In Vitro Erythropoiesis

Abstract: Cooperation between in vitro exogenous prolactin (PRL), granulocyte-macrophage colony-stimulating factor (GM-CSF), and interleukin-3 (IL-3) at an early step of in vitro erythroid differentiation has been shown in a previous study. To gain more insight into the role of PRL in in vivo hematopoiesis, we have now addressed the involvement of endogenous PRL in the growth of hematopoietic progenitors in a bone marrow (BM) stroma environment. The possible modulation of local PRL production by the inflammatory mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Prolactin (PRL) has been implicated as a regulator of haematopoiesis Lowenstein 1964, 1965;Bellone et al 1997;Abkowitz et al 2002;Akiyama et al 2005). Early studies demonstrated that PRL stimulates erythropoiesis in nonpregnant, pregnant and lactating mice Lowenstein 1964, 1965).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolactin (PRL) has been implicated as a regulator of haematopoiesis Lowenstein 1964, 1965;Bellone et al 1997;Abkowitz et al 2002;Akiyama et al 2005). Early studies demonstrated that PRL stimulates erythropoiesis in nonpregnant, pregnant and lactating mice Lowenstein 1964, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated that PRL stimulates erythropoiesis in nonpregnant, pregnant and lactating mice Lowenstein 1964, 1965). In addition, in vivo and in vitro studies have shown that PRL can increase the number of erythroid progenitors in haematopoietic tissue (Bellone et al 1997;Woody et al 1999;Richards and Murphy 2000;Welniak et al 2001). In the rat and mouse, mating activates twice-daily PRL surges for the first half of pregnancy; in addition, suckling during lactation is a wellestablished stimulus for PRL secretion (Erskine 1995;Soares 2004;Andrews 2005).…”
Section: Discussionmentioning
confidence: 99%
“…PRL has been shown to either interact with lymphohaemopoietic cytokines or mimic their action. Its co-operation with IL-2 in development of lymphokine-activated killer (LAK) cells 19±21 and with GM-CSF in maturation of CD34 + stem cells to erythropoietin (EPO)-responsive erythroid progenitors 16,17 has been documented by our group. Here we show that physiological concentrations of PRL (10±20 ng/ml) co-operate with GM-CSF in inducing monocytes to differentiate into DC, as judged by their morphological changes, expression of antigen-presenting and costimulatory molecules MHC II, CD80 and CD86, and ability to present alloantigens to CD4 T lymphocytes.…”
Section: Discussionmentioning
confidence: 90%
“…They thus become active T-cell stimulators. Because PRL has been shown by our group to interact with GM-CSF, 16,17 we have here addressed its possible involvement, alone or in combination with GM-CSF, in the process of DC maturation and antigen presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Both at presentation and in remission the majority of prolactin immuno-reactive cells in the marrow were interstitial mononuclear cells. Lymphoid cells produce prolactin (Montgomery, 2001), and stromal cells have a basal level of prolactin synthesis, which can be increased in response to cytokines (Bellone et al, 1997). It is possible that prolactin secretion might be upregulated as a result of interaction between the AML blasts and other bone marrow cells.…”
Section: S U M M a R Ymentioning
confidence: 99%